PERLINDUNGAN HUKUM BAGI DEBITUR YANG BERITIKAD BAIK DALAM PERJANJIAN OVER KREDIT: perlindungan hukum terhadap debitur yang beritikad baik dalam perjanjian over kredit dan cara membuktikan kriteria debitur yang beritikad baik dalam sebuah perjanjian hukum over kredit - Yuliza Anisa Fitri; Adlin Budhiawan (CV Rewang Rencang, 2024)
In protecting parties who have good intentions in an agreement, a legal umbrella is needed that can provide legal certainty protection, one of which is filing legal action through a judicial institution for debtors who feel disadvantaged as regulated in Article 1131 of the Civil Code, for further debtors who have good intentions in cases This person can claim rights to the documents and BPKB in question both through litigation and non-litigation. This legal protection is based on the principle of good faith in the continued debtor. From a civil law perspective, honesty or good faith is considered to always exist in every bezitter, whereas the existence of dishonesty or bad faith in a bezitter must be proven as regulated in Article 533 of the Civil Code.